Relevance of Violence with Social Well Being of Working Adolescents in Pakistan - Muhammad Ramzan, Muhammad Zakria Zakar,Shazia Qursehi & Zubair Ahmed Shah (Journal of Political Studies, 2013)
Violence permeates human life with its multidimensional consequences for the victims. Social significance of violence for children and adolescents has been a focus of both the sociologists and social psychologists. This is because of the very sensitive and crucial phase of adolescence where most of the trajectories and pathways shape human behavior along with socio-psychological and biological development. The present study explores the relevance of workplace violence with social well being of the 350 Pakistani adolescents working in 82 auto repair workshops. Conflict Tactics Scale (CTS-2) was used to measure intensity of violence whereas; social well being (SWB) was measured within five dimensions of Keyes’ (1998) model of social well being. Findings of the study revealed that violence against adolescents was highly correlated with their social well being. The demographic variables were also found to influence the correlation between violence against adolescents and their social well being.